Mechanisms of Cross-Shore Transport and Spatial Variability of Phytoplankton on a Rip-Channeled Beach - Fujimura, Atsushi G.; Reniers, Ad J. H. M.; Paris, Claire B.; Shanks, Alan L.; MacMahan, Jamie H.; Morgan, Steven G. (Frontiers in Marine Science, 2018)
We investigated whether cross-shore distributions of coastal phytoplankton to the surf zone are controlled by hydrodynamics and their biological characteristics. Data from a rip-channeled beach indicate that concentrations of phytoplankton are higher in the surf zone than offshore. To examine how phytoplankton is transported toward the shore, we used a coupled biophysical model, comprised of a 3D physical model of coastal dynamics and an individual-based model (IBM) for tracking phytoplankton on the rip-channeled beach. Waves and wind in the biophysical model were parameterized by the conditions during the sampling period. Previous studies indicated that growth rates of phytoplankton can be enhanced by high turbulence, which might contribute to high phytoplankton concentration in the surf zone. Some numerical and laboratory works showed that turbulence can also increase the downward velocity of phytoplankton, which could be carried by onshore bottom currents and remain in the surf zone. Furthermore, we adapted the IBM with the theoretical model of diurnal vertical migration (DVM) for phytoplankton. The theoretical DVM works as follows: in the morning, phytoplankton cells adhere to air bubbles and stay at the surface and close to the shore in the daytime because onshore wind and surface current direction is usually onshore; in the late afternoon, the cells switch their attachment from air bubbles to sand grains and sink to the bottom where the water flow is normally onshore at night. Finally, depth-varying growth of phytoplankton was also incorporated into the DVM module. Simulations using neutral passive particles do not give the expected results of observed patterns. All tested mechanisms, i.e., wind- and wave-driven currents, rip-current circulation, turbulence-driven growth and sinking, DVM, and depth-varying growth, enhanced onshore phytoplankton migration and cell concentrations in the surf zone, indicating that both biological traits and physical factors can be essential to phytoplankton cross-shore transport and spatial variability. Our model is open to be modified and re-parameterized, followed by further analysis and validation, so that it can be more adequate for ecological assessment of coastal areas.